Development of RAPD protocol for Shorea laevis - Siregar, U.J.; Sudarmonowati, E.; Sri Hartati, N. (1998)
To study genetic diversity of Shorea leavis using RAPD, optimization of the method is necessary to obtain good resolution. Two kinds of PCR conditions, emplyoing 109 random primers of Kit B, C,E, F, G and H from Operon Technology Ltd. were tried on S. laevis DNA extracted by CTAB miniprep method. It was found out that the most suitable PCR condition for S. laevis is condition, which require more PCR cycles, compunded with higher MgCl2, concentration, employed more DNA sample and primer. Further survey using two primers on 110 individuals from natural habitat showed that S.laevis has considerable amount of genetic variation